MOTOR DEVELOPMENT OF CHILDREN WITH VISUAL IMPAIRMENT - Ivana Sretenović; Goran Nedović (Human Research in Rehabilitation, 2019)
The aim of this study was to determine the level of motor development of children with visual impairment and comparison with peers of typical development. The research sample consisted of a total of 135 children with visual impairment and children with typical development, 7-10 years old, of both sexes. The Bruininks-Oseretsky Test of Motor Proficiency, 2nd edition was used to estimate motor development. The methods of descriptive statistics, as well as the T-test of independent samples, and the Hi square test were used in statistical processing of the obtained data. The results of the study had shown that the level of motor development of the subjects with visual impairment was below and well below the average for their age. Typical development subjects are mostly within the average norms.